• Предмет: Математика
  • Автор: fjjkjh
  • Вопрос задан 6 лет назад

решите уравнение (3x^2-2x)^2+16(3x^2-2x)-17=0

Ответы

Ответ дал: OverKnower
0
Заменим 3x^2-2х на t, получили

t^2 + 16t -17 = 0
a=1; b=16; c=-17
D = b^2 - 4ac = 16^2 - 4*1*(-17)=256+68=324, √D = 18
t1 = (-b+
√D)/2a = (-16+18)/2*1=2/2= 1
t2 = (-b-
√D)/2a = (-16-18)/2*1=-34/2= -17

Теперь подставляем получившиеся корни

1) 3x^2 - 2x = 1
    3x^2 - 2x - 1 = 0
    a=3; b=-2; c=-1
    D = 4+12 = 16; 
√D=4
    x1 = (2+4)/2*3 = 1           
    x2 = (2-4)/2*3 = -1/3

2) 3x^2 - 2x = -17
    3x^2 - 2x + 17 = 0
    a=3; b=-2; c=17
    D=4-204=-200; <0, значит корней нет

Ответ : x1=1; x2=-1/3
Похожие вопросы